Japin Ayun Anak Dance: A Collaborative Reflection on Ma'ayun Anak and Ba'ayun Mulud Traditions in South Kalimantan Banjar Community Culture - Putri Yunita Permata Kumala Sari; Rezky Rezky; Muhammad Jazuli; Juju Masunah; Wahyu Lestari (Universitas Negeri Semarang, 2023)
The Banjar people in South Kalimantan have a tradition of putting their children to sleep in a swing while chanting a rhythmic shalawat of Banjar poetry called Ma'ayun Anak. This tradition is integrated into the Ba'ayun Mulud tradition which is a cultural tradition of the Banjar people to ma'ayun a child in the month of Maulid or Rabiul Awwal in the Islamic calendar (Hijriyah) to celebrate the birthday of Rasulullah Muhammad Shalallahu 'Alaihi Wassalam. This cultural reflection collaborated and was expressed in a new dance creation entitled